2022
DOI: 10.3390/diagnostics12112716
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Thyroid Cancer Mortality and Incidence in Saudi Arabia: A 30-Year Study

Abstract: Thyroid cancer is the most prevalent endocrine cancer among the female population in the Kingdom of Saudi Arabia (KSA) and the ninth most common in the male population in Saudi Arabia. Over the past years, an increasing incidence of thyroid cancer has been reported in Saudi Arabia. However, the etiology of thyroid cancer is still not clear. Therefore, this study aimed to estimate thyroid cancer incidence and mortality trends in Saudi Arabia from 1990 to 2019. The current study utilized the Global Burden of Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 32 publications
(46 reference statements)
1
8
0
Order By: Relevance
“…Similarly, the luteinizing hormone (LH) and the follicle-stimulating hormone (FSH) get increased in menopausal females stimulating cancer growth 16 . Recent systematic reviews and meta-analyses have also con rmed an increased incidence rate of thyroid cancer with age in Saudi Arabia's population 17,18 . Age has been established as a critical factor in thyroid cancer patients' survivability [19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the luteinizing hormone (LH) and the follicle-stimulating hormone (FSH) get increased in menopausal females stimulating cancer growth 16 . Recent systematic reviews and meta-analyses have also con rmed an increased incidence rate of thyroid cancer with age in Saudi Arabia's population 17,18 . Age has been established as a critical factor in thyroid cancer patients' survivability [19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of age-adjusted thyroid cancer incidence rates and prevalence in Saudi Arabia are limited by the lack of regional variation data 17 . The age-standardized regional study revealed increased incidence and prevalence rates of thyroid cancer in Riyadh, Hail, Najran, Eastern, Jouf, and Tabuk, according to an analysis of the data in (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In Saudi Arabia, TC ranks as the most frequent endocrine cancer detected in women and the ninth most prevalent malignancy among men [ 10 , 11 ]. According to a recent study, the risk of TC in Saudi Arabia increased in both men and women between 1990 and 2019, amounting to 22- and 15-fold increases, respectively [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the death rate steadily increased by threefold in women and interestingly by sixfold in men in the same period. The author attributed the increase in the incidence rate to the advancement in the tools of detection and diagnosis [ 11 ]. Indeed; the most detected subtypes of TC were papillary adenocarcinomas, mixed papillary and follicular carcinoma, papillary microcarcinoma, papillary columnar cell carcinoma, and papillary carcinoma encapsulated subtypes, respectively [ 12 ].…”
Section: Introductionmentioning
confidence: 99%